It's a hard-knock life: Game load, fatigue, and injury risk in the National Basketball Association - Lewis, M. (Journal of Athletic Training, 2018)
Context: National Basketball Association (NBA) athletes experience a high rate of injuries. Injury prevention requires identifying observable and controllable risk factors.